Analyzing the influence of landscape pattern change on ecological water requirements in an arid/semiarid region of China - Zhao, Fen; Li, Hui; Li, Chunhui; Cai, Yanpeng; Wang, Xuan; Liu, Qiang (Journal of hydrology (Amsterdam), 2019)
•Calculating EWRs of vegetation the Penman-Monteith formula.•Quantitative analysis of correlation between landscape index and EWRs of vegetative ecosystem on different landscape scales.•The influences of landscape pattern changes on EWRs of vegetative ecosystem are obvious in an arid/semiarid region of China. With climate change and the intensification of human activities, landscape patterns have undergone important changes. These changes can have multiple impact on hydrology, nutrient transport between soil and vegetation and ecological function and health in vegetative ecosystems. Dynamic changes in landscape patterns may affect the ecological water requirements (EWRs) of vegetation. Based on meteorological data, soil data and 6 years of land use data (from 1990 to 2015), the EWRs were obtained through the Penman–Monteith formula. eight suitable landscape indices (Patch Density (PD), Connectivity Index (COHESION), Largest Patch Index (LPI), Aggregation Index (AI), Shannon Diversity Index (SHDI), Contagion Index (CONTAG), Separation Index (SPLIT), and Landscape Shape Index (LSI)) were used to explore the spatial and temporal characteristics of landscape patterns. Furthermore, the influences of landscape pattern changes on the EWRs of the middle main reaches of the Yellow River, China, were investigated. From 1990 to 2015, the total number of patches in the landscape pattern of the watershed increased, and the patch shape became more complex; the EWRs decreased from 392.7 mm to 276.5 mm, and the annual volume of the EWRs in the study area decreased from 124.8 × 108 m3 to 89.6 × 108 m3. The EWRs had a positive correlation with the LPI, indicating that the changes in the largest patch had a great impact on the EWRs. The EWRs also had a negative correlation with the SPLIT, showing that the more fragmented the landscape patches, the smaller the EWRs. With an increase in SHDI, the EWRs showed a downward trend. Furthermore, the EWRs showed a downward trend with decreasing CONTAG and COHESION. These results provide useful information for ecological restoration and provide an important reference for ecological environmental protection and the optimal allocation of water resources in arid/semiarid regions around the world. In the future, the EWRs can be regulated, and the utilization rate of water resources can be improved, by combining the current ecological environmental protection policies of the Yellow River Basin and managing future trends in landscape patterns.